Analysts’ recommendations in Brazil: do they add value? - Eid Júnior, William (2016)
This paper examines the value of analysts’ recommendations in Brazilian Stock Market. We studied a sample of 294 weeks of recommendations make public by the best seller newspaper in Brazil with six different investment strategies and time horizons. The main conclusion is that it is possible to beat the Brazilian market indexes Ibovespa and IBrX following the analysts’ stock recommendations. The best strategies are buying only the recommended stocks, buying the recommended stocks whose target and market prices difference is bigger than 25% and lesser or equal than 50%. The performance of the six strategies is analyzed through the use of bootstrap and Monte Carlo techniques.